Room-temperature workability of 6063 alloy for fitting clamps of overhead conductor lines. (January 2015) - Zeng, L.R.; Song, Z.M.; Wu, X.M.; Li, C.H.; Zhang, G.P.
Graphical abstract: Highlights: Compression tests were conducted at different strain rates and height reductions. Compression workability of the 6063 aluminum alloy was investigated. We obtained the deformation map related to deformation reduction and strain rate. We found that cracking occurred at GBs with misorientation angle more than 47°. Abstract: Compression workability of the 6063 aluminum alloy for fitting clamps to fasten and connect the aluminum alloy conductor lines was investigated under different height reductions and strain rates at room temperature. The deformation map for compression workability is obtained, which provides the critical deformation conditions related to deformation reduction and strain rate below which the 6063 alloy can be safely processed without cracking damage. Cracking damage behavior was investigated by electron backscattering diffraction technique, revealing that the compression-induced cracking of the 6063 alloy tends to occur at the grain boundaries with grain boundary misorientation angles more than 47°.